Architectural Peculiarities of the Structure of Technoparks and Technopolises - Olimova, Odina (Sustainable Civil Building Management and Engineering Journal, 2024)
This research aims to explore the architectural features that define modern technoparks and technopolises as innovative hubs for knowledge-based industries worldwide. By analyzing various case studies from leading global centers, we seek to identify commonalities in design principles, spatial organization, and urban planning strategies that contribute to their success as catalysts for technological advancement and economic growth. Through a comprehensive analysis of diverse case studies, this study identifies recurring design principles, spatial arrangements, and urban planning methodologies that underpin their efficacy as drivers of technological progress and prosperity. The methodology involves an in-depth examination of case studies from prominent technoparks and technopolises worldwide. Analysis is conducted to identify recurring patterns in architectural design, spatial organization, and urban planning strategies. By synthesizing findings from these case studies, this research elucidates the critical factors shaping the architectural landscape of technoparks and technopolises. The results highlight the importance of functionality, aesthetics, and sustainability in architectural design to foster collaboration, creativity, and innovation within these complexes. Spatial organization prioritizes connectivity and accessibility, facilitating interaction among stakeholders and promoting a conducive environment for knowledge exchange and interdisciplinary collaboration. Furthermore, integration of amenities such as green spaces and mixed-use developments enhances the quality of life for occupants and contributes to the overall vibrancy of these innovation clusters. In conclusion, the architectural peculiarities of technoparks and technopolises play a significant role in shaping their identity as catalysts for technological advancement and economic prosperity. Understanding these architectural features provides valuable insights for policymakers, urban planners, and architectural practitioners to strategically plan and sustainably develop technologically-driven urban environments. Leveraging design innovation can cultivate vibrant innovation ecosystems, propelling societies towards a more sustainable and knowledge-driven future.